If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(6x + -9) = 9 Reorder the terms: -1(-9 + 6x) = 9 (-9 * -1 + 6x * -1) = 9 (9 + -6x) = 9 Add '-9' to each side of the equation. 9 + -9 + -6x = 9 + -9 Combine like terms: 9 + -9 = 0 0 + -6x = 9 + -9 -6x = 9 + -9 Combine like terms: 9 + -9 = 0 -6x = 0 Solving -6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-6'. x = 0 Simplifying x = 0
| f(-5)=3.5x-6 | | 7x-8=7-31 | | f(-5)=3.5-6 | | 8=21p/100 | | 12y+13-3y-7= | | f(x)=3.5x-6 | | 4/q=5 | | X=6.2(180-x) | | 7(-6+-5)=(7*g)+(7*-5) | | 16x+3x+2x+x= | | 4a+8=2a-6 | | (2/7n-3m)^2 | | y=log(13-x) | | 3(6y-1)=6 | | Fx=x^4-9x^2+18 | | (x-2)=2(x+3)+7 | | S+15*-2=-10 | | -3a+10=2a | | S+15=20 | | 12(2w-5)=6w+3(5x-4) | | 3x+2=6x+24 | | y-2.9=5.3 | | 9k-3=40 | | 9+.875r=3 | | a+14=3A | | 9k+3=40 | | y^2+2y+4x-8=0 | | 3(11x+1)= | | x+Ln(x)+-3=0 | | 8y-1(5y+2)=16 | | x+ln(x)-3=0 | | Y=0.494(3)-974.5 |